2001
DOI: 10.2337/diacare.24.5.881
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hypoglycemia With the GlucoWatch Biographer

Abstract: OBJECTIVE -Hypoglycemia is a common acute complication of diabetes therapy. The GlucoWatch biographer provides frequent and automatic glucose measurements with an adjustable low-glucose alarm. We have analyzed the performance of the biographer low-glucose alarm relative to hypoglycemia as defined by blood glucose Յ3.9 mmol/l. RESEARCH DESIGN AND METHODS -The analysis was based on 1,091 biographer uses from four clinical trials, which generated 14,487 paired (biographer and blood glucose) readings.RESULTS -The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…At the fitted equal to 19.6 min, the blood glucose concentration is 58.5 mg/dL, which agrees well with the independently determined dividing point between normoglycemia and hypoglycemia (19). Therefore, we divide the quantitative measurements of glucose concentration, rO 2 , <C Hb >, <sO 2 >,∇sO 2 , and v f into two phases, as marked by the two colors in Fig.…”
Section: Quantitative Measurement Of Oxygen Release From Single Rbcs Insupporting
confidence: 58%
“…At the fitted equal to 19.6 min, the blood glucose concentration is 58.5 mg/dL, which agrees well with the independently determined dividing point between normoglycemia and hypoglycemia (19). Therefore, we divide the quantitative measurements of glucose concentration, rO 2 , <C Hb >, <sO 2 >,∇sO 2 , and v f into two phases, as marked by the two colors in Fig.…”
Section: Quantitative Measurement Of Oxygen Release From Single Rbcs Insupporting
confidence: 58%
“…Concerning the detection of hypoglycemia, the Glucowatch Biographer does not appear as an accurate device according to the ADA criteria (18). In a recent study, the sensitivity of Glucowatch to detect hypoglycemic episodes was only 24% when considering 3.9 mmol/l as the threshold of hypoglycemia, whereas specificity was 99% (19). In contrast, a study carried out to evaluate the accuracy of Glucoday, a microdialysis fiber inserted subcutaneously, showed that 97% of the 381 data pairs fell in the A and B regions of the error grid analysis (20).…”
Section: Reproducibilitymentioning
confidence: 99%
“…GlucoWatch biographer (Satish et al, 1999;Rao et al, 1993;Pitzer et al, 2001) allows frequent, automatic and minimally invasive glucose monitoring. It performs three readings per hour for 12 h after calibration.…”
Section: Introductionmentioning
confidence: 99%